The Role of Teachers and Parents of Online Learning in Primary School During the Covid-19 Pandemic Era - Nurasiah, Nurasiah; Solehuddin, M (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2021)
As a country greatly affected by the Covid-19. Indonesia applies a large-scale social restriction (LSRR) in many provinces, especially in West Java. The execution of LSSR insists that people stay and work at home. Schools are physically closed and teaching-learning is organized and delivered online. Teachers provide teaching services online, while students learning independently at home. Learning from home is one solution for the learning process to keep it organized. Because learning that should be done face-to-face in class is now being done by utilizing technology, namely online learning. Writing this article aims to identify the role between teachers and parents who have a role in the online learning process during the Covid-19 pandemic, both before learning begins, when learning takes place, until after learning is complete. The author uses the literature study method from various references related to the role of teachers and parents so that the objectives of online learning can be achieved optimally.